2020
DOI: 10.4103/jfmpc.jfmpc_385_20
|View full text |Cite
|
Sign up to set email alerts
|

Level of awareness of diabetic ketoacidosis among diabetes mellitus patients in Riyadh

Abstract: Background: Diabetic ketoacidosis (DKA) is considered to be a serious acute life-menacing complication of diabetes type (1) and type (2). The study aims to assess the level of awareness regarding DKA among diabetic patients in the Riyadh population. Methodology: The study is an institution-based cross-sectional study with a sample size of 150 participants. The participants are chosen through systemic random sampling, who have type (1) or type (2) diabetes mellitus patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
4
6
0
Order By: Relevance
“…Consistent with our findings, Alanazi et al [5] reported that more than half (54%) of the diabetic patients in Riyadh City, Saudi Arabia, demonstrated low knowledge about the risk factors of DKA. Our reports were likewise in line with Satti et al's publication [8].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our findings, Alanazi et al [5] reported that more than half (54%) of the diabetic patients in Riyadh City, Saudi Arabia, demonstrated low knowledge about the risk factors of DKA. Our reports were likewise in line with Satti et al's publication [8].…”
Section: Discussionsupporting
confidence: 93%
“…About the symptoms, DKA patients usually presented with polyuria with polydipsia (98%), weight loss (81%), muscles fatigue (62%), dyspnea (57%), vomiting (46%), and preceding illness (40%). These symptoms can damage the respiratory and digestive systems, resulting in respiratory failure and severe abdominal discomfort, which can lead to a coma and death [ 8 ]. Many studies worldwide have measured DKA awareness and practice among people with diabetes and their caregivers; few studies have measured in Saudi communities.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the awareness and knowledge of the caregivers regarding the symptoms, signs and complications of DKA, this study seems to reflect better results compared to previous studies, like that by Farran et al (2020) who found that 38.67% of our participants have a poor awareness regarding DKA complications [15]. However, the percentages of those who reported DKA could lead to coma (285; 68.8%) are comparable to the 59.3% they found in the same study.…”
Section: Discussionsupporting
confidence: 56%
“…46.8% of the patients appeared to have poor awareness levels, 29.2% were moderate and only 24% were shown to have a good understanding of the disease. Several studies established a low level of awareness in patients and their caregivers [1,7,[15][16][17][18][19][20]. However, in Palestine [19], hypertensive individuals scored higher on total knowledge and attitude toward chronic renal disease prevention and early detection.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a collection of metabolic abnormalities defined by elevated blood glucose levels caused by a deficiency in circulating insulin, insulin resistance, or overproduction of hormones that inhibit insulin function [ 1 ]. From an epidemiological point, diabetes mellitus is one of the most common causes of death, disability, and economic loss worldwide.…”
Section: Introductionmentioning
confidence: 99%